Application of new WHO classification on malignancies of sinonasal tract: correlation with epidemiology and survival in Pakistani population - Waseem, Zainab; Mushtaq, Sajid; Hassan, Usman; Hussain, Mudassar; Loya, Asif; Hussain, Raza; Jamshaid, Arif (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the clinicopathological characteristics of sinonasal malignancies in the light of the updates regarding head and neck tumours. Method: The retrospective study was conducted at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised data of patients diagnosed with primary malignant tumours of the sinonasal tract between 2015 and 2020. Slides related to biopsies and resection specimens were retrieved from the institutional database and reviewed by two pathologists. Follow-up data was also obtained. Data was analysed using SPSS 20. Results: Of the 245 samples, 144(58.7%) were epithelial tumours, 46(18.7%) neuroectodermal tumours, 41(16.7%) hematolymphoid tumours and 14(5.7%) were malignant soft tissue tumours. A heavy reliance was placed on immunohistochemical stains to diagnose poorly-differentiated tumuors. Survival was dismal, especially with early and frequent spread to the brain (33.3% in cases of Sinonasal Undifferentiated Carcinoma). Conclusion: A wide array of sinonasal malignancies was seen. Updated knowledge of the malignancies prevalent in the region is imperative for timely diagnosis and treatment. Key Words: Sinonasal tract, Squamous cell carcinoma, Sinonasal undifferentiated carcinoma, NUT c, Survival, Pakistani.